Toddlers Categorically Perceive Emotional Facial Expressions Along a Happy–Sad Continuum. (August 2020) - Lee, Vivian; Da Silva, Natasha; Rutherford, M. D.
Adults perceive a continuum of emotional facial expressions categorically rather than continuously. Categorical perception is thought to be adaptive and functional, allowing for inferences that inform behavior. To date, studies have demonstrated categorical perception of some emotional facial expressions in infants. However, a recent study reported that 12-month-olds infants do not perceive facial emotional expressions categorically across a happy–sad continuum. In contrast, toddlers at 3.5 years of age appear to use categorical perception along the happy–sad continuum. Using a novel paradigm that employed the use of a looking-time discrimination task and an explicit identification task, this study measured 26-month-old's identification of faces and ability to discriminate between faces along a happy–sad continuum. Results suggest that 26-month-olds perceive facial expressions categorically along the happy–sad continuum.